L’enseignant spécialisé chargé de l’aide à l’école primaire : un métier en (re)construction - Serge Thomazet; Pascale Ponté; Corinne Mérini (Recherches en Éducation)
In French primary schools, SEN teachers in charge of helping children with learning difficulties (maîtres E) see their job rigorously questioned and transformed. We present the findings of research which has allowed us to explore, through their collaborative practice, the work of experienced SEN teachers. The research aims to determine the evolution and reconfiguration of this practice during the transition stage. Faced with the complexity of the object of our research, we combined the methodologies and dual analyses of sociology of organizations (Crozier & Friedberg, 1977) and ergonomic psychology (Leplat, 1980). Consistent with this underpinning, we carried out a formal, qualitative, longitudinal study. Results show the existence of tensions within the profession, especially between SEN teachers and colleagues. These tensions reveal the presence of an area of dynamic, changing collaboration, likely to bring about a shift in what the job means and encompasses. First, a fundamental shift, shared by all, from the role of primary school teacher to that of SEN teacher; next a shift which leads SEN teachers, under prescriptive pressure, to adopt new practices of indirect support, organised as a system, including those involved (parents, class and SEN teachers, other professionals.)